Formal firms with bribery in a dynamic business environment - Vu, Hoang Nam (Journal of business ethics, 2024)
While there are a relatively large number of studies on the relationship between firm formality and bribery, little is known about how a dynamic business environment affects this relationship. Using longitudinal data collected from biennial surveys of small- and medium-sized firms in Vietnam, this study shows that formal firms are more likely to pay bribes, which are proxied by greasing and rent-seeking bribes, than informal firms in provinces with poor business environments. Nevertheless, when the quality of the local business environment is improved, the formal firms are less likely to commit bribery. They also pay less bribes and have an expectation of paying less bribes in the future. These findings suggest that the focus of anti-corruption strategies should be on improving the quality of the local business environment to support the formal small- and medium-sized firms.